2020
DOI: 10.3126/jota.v3i1.31356
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Pandemic and its Impact on Tourism Industry in Nepal

Abstract: The article aims to measure the impact of novel corona virus disease (COVID-19) pandemic on tourism industry in Nepal. The pause of tourism mobility for months due to an abrupt halt of transportation means; shuttered borders; and stay-at-home orders by government has brought adverse effects on Nepal’s tourism industry and its stakeholders. Likewise, airlines, accommodation, transport operators and other sub-sectors of Nepal are suffering due to international travel bans. There are spillover impacts of the pand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 19 publications
0
25
0
Order By: Relevance
“…Naumov et al (2020) identified that Bulgarian tourists did not generally trust the sanitation measures and cleanliness at chain-branded hotels and preferred to seek accommodation at guest houses. Ulak (2020) have reported the effects of COVID-19 on the tourism industry in Nepal in general, and did not include the effects on SMHs. It is important to note that the survival of SMHs during, and the extent to which they can recover from, the crisis also depends on how a crisis affects their operators personally.…”
Section: Ebola Virusmentioning
confidence: 99%
“…Naumov et al (2020) identified that Bulgarian tourists did not generally trust the sanitation measures and cleanliness at chain-branded hotels and preferred to seek accommodation at guest houses. Ulak (2020) have reported the effects of COVID-19 on the tourism industry in Nepal in general, and did not include the effects on SMHs. It is important to note that the survival of SMHs during, and the extent to which they can recover from, the crisis also depends on how a crisis affects their operators personally.…”
Section: Ebola Virusmentioning
confidence: 99%
“…Hence, this practice will boost up the confidence level of flaccid travelers and motivates them to travel once again. Scholars are advocating tourism will revive through the domestic tourist movement and gradually international tourist mobility will help provide oxygen and spectrum to the tourism industry which has gone to coma being a patient of COVID-19 (Ulak, 2020). The tourism sector is likely to lose 85 thousand direct jobs and 36 thousand indirect jobs amounting to a total job loss of 121 thousand (Shivakoti, 2021).…”
Section: Future Of Buddhist Tourismmentioning
confidence: 99%
“…Another strategy revealed by the study concerning how the porters and guides have managed to survive the COVID-19 pandemic economic impact is through engaging in other income generating activities (Ulak, 2020). Few had these projects and activities but many had no these activities before COVID-19 pandemic.…”
Section: Engaging In Other Income Generating Activitiesmentioning
confidence: 99%
“…Nepal also suffered the consequences; jobs in hotels and tourism industry were cut off. Almost about 200,000 people who were directly employed in hotels, restaurants, hiking, airlines, mountaineering and other subsectors in tourism industry remain jobless (Asian Development Bank, 2019;Ulak, 2020). The recovery of international tourism after pandemic is expected first with some specific regions like European regions, but domestic tourism is expected to recover more quickly.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation